Active learning for middle school based on information technology in SMA Negeri 1 Dolok Batu Nanggar - Marpaung, T.J.; br. Ginting, Dewi Sartika; Candra, Andy; Marpaung, J.L. (Talenta Publisher, 2020)
After the millennium era, with the rapid development of information technology, changes in business patterns also increased sharply. This is what is called the era of disruption. IT technology has also penetrated the world of education, both in management and in learning methods. In the world of education, now the learning method does not only use conventional methods such as from textbooks and explanations from teachers, but also with effective and efficient learning methods by utilizing information technology. An example is multimedia-based learning media. Community service is one way that can be used to carry out information technology socialization. Community service that will be carried out in this research is entitled Utilization of Information Technology in the Implementation of Active Learning in SMA Negeri 1 Dolok Batu Nanggar in Facing the Era of the Industrial Revolution 4.0, with the aim of helping teachers in a more interesting interactive and fun mathematics learning process, because In general, junior high school students have used a lot of telecommunications devices equipped with various kinds of multimedia. The learning application that is built includes material, exercises and tests, in accordance with applicable competency standards. Furthermore, training will be given to several senior high schools, as a provision on how to prepare and use this learning system application so as to increase student motivation and ultimately increase student achievement and improve the quality of education.